2001
DOI: 10.3168/jds.s0022-0302(01)74591-2
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Bifidobacteria on Lipid Peroxidation in the Colonic Mucosa of Iron-Overloaded Mice

Abstract: The antioxidative effects of live bifidobacteria on lipid peroxidation in the colonic mucosa were investigated. Bifidobacterium bifidum strain Yakult, which has been used for production of fermented milk, most effectively inhibited lipid peroxidation catalyzed by ferrous iron in liposomes among 10 species of bifidobacteria from human intestinal flora. Oral administration of B. bifidum strain Yakult for 2 wk significantly decreased the level of lipid peroxide (thiobarbituric acid reactive substance) in the colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…In previous studies, oral administration of Bifidobacterium bifidum strain Yakult effectively decreased colonic oxidative stress induced by an iron overload diet (17,18). It has also been reported that Streptococcus thermophilus YIT 2001 protected the colonic mucosa against oxidative stress (17).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, oral administration of Bifidobacterium bifidum strain Yakult effectively decreased colonic oxidative stress induced by an iron overload diet (17,18). It has also been reported that Streptococcus thermophilus YIT 2001 protected the colonic mucosa against oxidative stress (17).…”
Section: Discussionmentioning
confidence: 99%
“…Some reported benefits include enhanced immune system [5] and defense against pathogens [6], modulation of short-chain fatty acid (SCFA) production [7] and tight junction integrity [8], and mild improvement in iron status [9]. Proliferation of beneficial bacteria, usually lactobacilli and bifidobacteria, in the colon of the host may also be associated with reducing lipid peroxidation in colonic mucosa of intact mammals [10] [11]. The putative antioxidant effect might be due to the ability of the bacteria to scavenge free radicals, and/or an increase in antioxidant capacities of the colon contents.…”
Section: Introductionmentioning
confidence: 99%
“…Mucosal lipid peroxide was measured by using the thiobarbituric acid reactive substance (TBARS) assay reported previously. 13) TBARS is expressed as the malondialdehyde (MDA) equivalent.…”
Section: Methodsmentioning
confidence: 99%